Health in development - Sen, Amartya (1999)
Concludes firstly that the enhancement of health is a constitutive part of development; secondly given other things, good health and economic prosperity tend to support each other; thirdly enhancement of good health can be helped by a variety of actions, including public policies; fourthly even when an economy is poor, major health improvement can be achieved through using the available resources in a socially productive way; and, fifthly the issue of social allocation of economic resources cannot be separated from the role of participatory politics and the reach of informed public discussion.